Surgical management of post-infarction ventricular septal defect, mitral regurgitation and ventricular aneurysm. Issue 9 (7th September 2019) - Belete, Samuel; Punjabi, Karan; Afoke, Jonathan; Anderson, Jonathan
ABSTRACT: A 49-year-old diabetic male was admitted to a hospital in 2018 following a 3-week history of worsening dyspnoea and pedal oedema. Early review and investigations indicated acute heart failure. Transthoracic echocardiogram (TTE) revealed mitral regurgitation (MR), aneurysmal change of the ventricles, a ventricular septal defect (VSD) and systolic dysfunction. Coronary angiogram demonstrated a significant left anterior descending and right coronary artery disease. He was diagnosed with a late presenting myocardial infarction (MI) with secondary mechanical complications. Mechanical complications of MI frequently require surgical intervention. The patient underwent a repair of VSD, mitral valve repair, excision of aneurysmal segment and coronary artery bypass grafting. Post-operative recovery was complicated by a sternal wound infection managed in conjunction with the plastic surgeons. A post-operative TTE showed a repaired ventricular septum and no residual MR. Early recognition and appropriate medical optimisation are required to achieve good patient outcomes.